Effects of respiratory and non-respiratory factors on disability among older adults with airway obstruction: The Cardiovascular Health Study. (1st October 2013) - Locke, Emily; Thielke, Stephen; Diehr, Paula; Wilsdon, Anthony G.; Graham Barr, R.; Hansel, Nadia; Kapur, Vishesh K.; Krishnan, Jerry; Enright, Paul; Heckbert, Susan R; Kronmal, Richard A.; Fan, Vincent S.
Abstract Background: High rates of disability associated with chronic airway obstruction may be caused by impaired pulmonary function, pulmonary symptoms, other chronic diseases, or systemic inflammation. Methods: We analyzed data from the Cardiovascular Health Study, a longitudinal cohort of 5888 older adults. Categories of lung function (normal; restricted; borderline, mild-moderate, and severe obstruction) were delineated by baseline spirometry (without bronchodilator). Disability-free years were calculated as total years alive and without self-report of difficulty performing &γτ;1 Instrumental Activities of Daily Living over 6 years of follow-up. Using linear regression, we compared disability-free years by lung disease category, adjusting for demographic factors, body mass index, smoking, cognition, and other chronic co-morbidities. Among participants with airflow obstruction, we examined the association of respiratory factors (FEV1 and dyspnea) and non-respiratory factors (ischemic heart disease, congestive heart failure, diabetes, muscle weakness, osteoporosis, depression and cognitive impairment) on disability-free years. Results: The average disability free years were 4.0 out of a possible 6 years. Severe obstruction was associated with 1 fewer disability-free year compared to normal spirometry in the adjusted model. For the 1, 048 participants with airway obstruction, both respiratory factors (FEV1 and dyspnea) and non-respiratory factors (heart disease, coronary artery disease, diabetes, depression, osteoporosis, cognitive function, and weakness) were associated with decreased disability-free years. Conclusions: Severe obstruction is associated with greater disability compared to patients with normal spirometery. Both respiratory and non-respiratory factors contribute to disability in older adults with abnormal spirometry.